A Qualitative Exploration of Collective Collapse in a Norwegian Qualifying Premier League Soccer Match—The Successful Team's Perspective - Schei, Gaute S.; Haugen, Tommy; Jones, Gareth; Sæther, Stig Arve; Høigaard, Rune (Frontiers in Psychology, 2022)
The case in the current study is a crucial match in the qualification for the Norwegian Premier League (Eliteserien). In the match, the study participants experience a radical change of performance towards the end of the second half, from being behind by several goals, they score 3 goals in 6 minutes and thus win the qualifying game. The purpose of this study was therefore to examine players 'and coaches' (sporting director) perceptions and reflections on what happened in their own team and in the opposing team. The momentum shift in the opposition team can be described as a collective collapse. In the study the collective collapse process model was used as a theoretical departure and as guide for designing the questions and the content where five semistructured interviews were conducted with participants in the match (players, coach, sporting director). They watched excerpt clips from the match to recall the main events, which they subsequently reflected on. The results highlighted the importance of the “before-game” aspects (i.e., pressure, first game result), the “during-the-game” behavior (i.e., goals scored, playing with a low degree of risk) and the cognitive (i.e., feelings of pressure, despair) and emotional (i.e., frustration, joy) reactions of the match unfolding. In addition, social contagion processes were prevalent in both teams related to emotion and behavior. Overall, the data from this study investigated the general structure of the process model of collective sport team collapse and found support for the notion of a temporal cascade of causes for a team collapse. Future research is encouraged to examine this model, to provide guidance to teams, coaches, and sport psychologists in order to make recommendations for dealing with collective collapse in sport teams.